2016
DOI: 10.1002/pbc.26193
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second cancers after radiotherapy and systemic chemotherapy in heritable retinoblastoma survivors: A report from the German reference center

Abstract: Second cancers remain a major concern in heritable retinoblastoma survivors. Consistent with previous reports, radiotherapy increased second cancer incidence and influenced type and localization. However, chemotherapy was the strongest risk factor for second malignancies outside the periorbital region. Our results provide screening priorities during life-long oncological follow-up based on the curative therapy the patient has received and emphasize the need for less-detrimental therapies for children with heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 47 publications
4
76
4
2
Order By: Relevance
“…A recent study demonstrated an increased risk of second cancers in the setting of EBRT plus chemotherapy (40-year cumulative incidence of 54.2% vs. 37.1% with EBRT alone; ref. 25). In contrast, brachytherapy did not change the incidence ratio of second cancers compared with enucleation or other focal treatments alone.…”
Section: Hereditary Rb: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…A recent study demonstrated an increased risk of second cancers in the setting of EBRT plus chemotherapy (40-year cumulative incidence of 54.2% vs. 37.1% with EBRT alone; ref. 25). In contrast, brachytherapy did not change the incidence ratio of second cancers compared with enucleation or other focal treatments alone.…”
Section: Hereditary Rb: Introductionmentioning
confidence: 80%
“…The risk of second malignant neoplasms is about 20% in individuals with hereditary RB who have not received radiotherapy and substantially higher (40%-50%) in those that have been irradiated (19,25). We, therefore, recommend consideration of second primary tumor surveillance for all carriers of pathogenic RB1 germline mutations regardless of previous radiation.…”
Section: Second Malignant Neoplasms Among Rb1 Mutation Carriersmentioning
confidence: 99%
“…In this cohort, four of the six patients that developed SPM were also treated with EBRT and the risk of SPM remained low in those treated with intravenous chemotherapy alone 20. Temming et al reported no significant difference in SPM development if treated with enucleation or focal therapy compared with systemic chemotherapy 18. Lastly, it is also well known from the retinoblastoma literature as well as paediatric cancer literature that alkylating agents and topoisomerase inhibitors increase the risk of secondary acute myeloid leukemia 5 7 11…”
Section: Discussionmentioning
confidence: 74%
“…Osteosarcoma is the leading cause of death in RB survivors [136]. Receiving radiation therapy and systemic chemotherapy are important risk factors for developing osteosarcoma in RB patients [137]. …”
Section: Figurementioning
confidence: 99%